International handbook of adult mortality - Rogers, Richard G.; Crimmins, Eileen M.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This handbook presents a comprehensive and up-to-date overview of unprecedented substantive, theoretical, methodological, and statistical developments and insights, and an in-depth examination of trends and patterns, in adult mortality around the world. With over two dozen chapters and more than fifty authors, this volume draws from top international mortality experts to provide one of the best overviews of life expectancy extant. The handbook documents remarkable gains in life expectancy, which stand out as one of the most important accomplishments of the twentieth century. Individuals in more developed countries can expect to live longer now than ever before, especially the Japanese, who enjoy record-setting life expectancies. The book also explores unfortunate declines in life expectancy in selected countries brought on by such factors as the following: infectious diseases; accidents, suicides, and homicides; and political and economic conflict and turmoil. This book synthesizes the wealth of mortality information available, clearly articulates the central findings to-date, identifies the most appropriate datasets and methods currently available, illuminates the central research questions, and develops an agenda to address these research questions. The authors carefully examine central factors related to mortality, including health behaviors, socioeconomic status, social relations, biomarkers, and genetic factors. The book will prove especially relevant to researchers, students, and policy makers within social and health sciences who want to better understand international trends and patterns in adult mortality. - publisher's description.
Introduction Mortality Framework and Context Richard Rogers and Eileen Crimmins Part 1: Historical Trends Chapter 1. Historical Trends in Mortality France Meslé and Jacques Vallin, INED Part 2: Temporal and Spatial Trends Associated with Mortality Chapter 2. Comparative International Trends: Europe Marc Luy, Christian Wegner, Wolfgang Lutz, IIASA, and Vienna Institute of Demography, Austrian Academy of Sciences Chapter 3. Adult Mortality in the Former Soviet Union Michael Murphy, London School of Economics Chapter 4. Latin America and the Caribbean from 1850 to the Present Alberto Palloni, Northwestern University Chapter 5. Adult Mortality in Asia Zhongwei Zhao, Australian National University Chapter 6. Adult Mortality Trends in Africa Georges Reniers, Princeton University, Bruno Masquelier, UCL, Belgium, and Patrick Gerland, UN Chapter 7. Global Trends in AIDS Mortality John Bongaarts, Population Council, and François Pelletier, United Nations Population Division, and Patrick Gerland, UN Pop. Division Part 3: Sociodemographic, Economic, and Psychological Determinants of Mortality Chapter 8. Early Life Conditions and Later Life Mortality Jennifer Karas Montez Mark Hayward, University of Texas at Austin Chapter 9. Age Patterns in Adult Mortality, with a Focus on Centenarians Jean-Marie Robine, INSERM Chapter 10. Sex and Gender Differences in Mortality Richard G. Rogers, Bethany G. Everett, and Robert J. Kemp, University of Colorado Chapter 11. The Hispanic Paradox Kyriakos S. Markides and Karl Eschbach, University of Texas Medical Branch Chapter 12. Educational Attainment and Adult Mortality Robert A. Hummer and Joseph T. Lariscy, University of Texas at Austin Chapter 13: Work, Occupation, Income, and Mortality Patrick Krueger, University of Texas School of Public Health, and Sarah A. Burgard, University of Michigan Chapter 14. The Influence of Health Behaviors on Mortality Christine L. Himes, Syracuse University Chapter 15. Discrimination, Chronic Stress, and Mortality among Black Americans: A Life-Course Framework James Jackson, Darrell Hudson, Kiarri Kershaw, Briana Mezuk, Jane Rafferty, and Katherine Knight Tuttle, University of Michigan Chapter 16. Self-Rated Assessments of Mortality Marja Jylhä, University of Tampere, Finland Chapter 17. Religion and Adult Mortality Ellen Idler, Rutgers University Part 4: Biological Risk Factors Chapter 18. Links between Biomarkers and Mortality Eileen Crimmins and Sarinnapha Vasunilashorn, University of Southern California Chapter 19. Genetic Factors and Adult Mortality Kaare Christensen, University of Southern Denmark, and James W. Vaupel, Max Planck Institute for Demographic Research Part 5: Contextual Effects on Mortality Chapter 20. Neighborhood Effects on Mortality Arijit Nandi and Ichiro Kawachi, Harvard University Chapter 21. Health and Mortality Consequences of the Physical Environment Christopher Browning, Ohio State University, Eileen E. Bjornstrom, University of Missouri, and Kathleen A. Cagney, University of Chicago Part 6: Classification of Causes of Death Chapter 22. Coding and Classifying Causes of Death: Trends and International Differences Robert N. Anderson, National Center for Health Statistics Chapter 23. Avoidable Mortality: A Review Hiram Beltrán-Sánchez, University of Southern California Part 7: Mathematical and Modeling Approaches to Mortality Chapter 24. Model Schedules of Mortality Patrick Heuveline, UCLA and Sam Clark, University of Washington Chapter 25. Period versus Cohort Mortality Michel Guillot, University of Pennsylvania Chapter 26. Healthy Life Expectancy Carol Jagger, University of Leicester, and Jean-Marie Robine, French Institute of Health and Medicinal Research, INSERM Part 8: Government Policies Designed to Affect Mortality Chapter 27. Mortality Avoidable by Health Care and Public Health and Policy Interventions Luc Bonneux, NIDI Chapter 28. Government Policies Intended to Influence Adult Mortality S. Jay Olshansky, University of Illinois at Chicago, and Dana Goldman, RAND Conclusion Richard Rogers and Eileen Crimmins.
Electronic reproduction.
Keywords: Mortality -- Handbooks, manuals, etc; Electronic books